Mitigation of waste threats to the environment through plastic waste management - Dwi Jati Marta (Indonesian Red Crescent Humanitarian Journal, 2025)
Plastics and plastic-based products are increasingly used for various purposes alongside technological, industrial, and population growth because they are lightweight, strong, flexible, easily molded, corrosion-resistant, easy to color, effective thermal and electrical insulators, and relatively affordable. This study employs a qualitative method with a descriptive approach. The purpose of this study is to provide an overview of governmental mitigation efforts in addressing waste-related threats through plastic waste management. The results indicate that Indonesia generates approximately 3.2 million tons of plastic waste entering the oceans annually, positioning it as the second-largest contributor globally after China. Consequently, Indonesia is the largest contributor of plastic waste in Southeast Asia, with plastic materials requiring hundreds of years to degrade. Excessive plastic waste adversely affects human health and the environment and may eventually lead to hazards such as flooding as well as air and soil pollution. Therefore, mitigation through effective plastic waste management is necessary to reduce the risks associated with excessive waste. Such mitigation may be implemented through technological, social, economic, cultural, and institutional approaches. Technological approaches include the application of pyrolysis, hydrothermal methods, and the use of environmentally friendly raw materials. Social and cultural approaches encompass public awareness activities and community engagement. The circular economy framework may also be applied as an economic approach. The institutional approach involves the participation of central and local governments in implementing existing policies and regulations, as well as formulating new regulatory measures aimed at reducing plastic waste.